2016
DOI: 10.3390/su8101065
|View full text |Cite
|
Sign up to set email alerts
|

Resident Knowledge and Willingness to Engage in Waste Management in Delhi, India

Abstract: Abstract:Delhi generates about 8360 tons of municipal solid waste per day, and there is low compliance to rules regarding waste management. The objective of this paper was to understand the situation in Delhi with respect to the segregation, storage, collection, and disposal of household waste, and to assess the knowledge of the residents of Delhi, and their willingness to engage in solid-waste management. A stratified random sample, comprising 3047 respondents, was chosen for a questionnaire survey, covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 37 publications
4
25
0
2
Order By: Relevance
“…The culture of separation does not exist in the city and the lack of selective collection routes or incentive programs for recycling in homes influences the bad practices of separation that are associated with the three main difficulties found in the survey applied. This culture leads to recyclers being exposed to occupational hazards ( Figure 1), because they usually always go behind a collection truck trying to recycle some of the garbage that is generated in their work zones, only recovering the recyclable waste which is 3% of the total waste generation by the city, a percentage similar to those found in Delhi, India, in which only 2% of the population recycle [38,39]. The results found in this work contrast with those found by other authors [40], which the same results are shown that some of the recyclers have an intermediate school level and many of them have begun to work from children in the streets, and are even affected families.…”
Section: Quantitative Stagementioning
confidence: 99%
“…The culture of separation does not exist in the city and the lack of selective collection routes or incentive programs for recycling in homes influences the bad practices of separation that are associated with the three main difficulties found in the survey applied. This culture leads to recyclers being exposed to occupational hazards ( Figure 1), because they usually always go behind a collection truck trying to recycle some of the garbage that is generated in their work zones, only recovering the recyclable waste which is 3% of the total waste generation by the city, a percentage similar to those found in Delhi, India, in which only 2% of the population recycle [38,39]. The results found in this work contrast with those found by other authors [40], which the same results are shown that some of the recyclers have an intermediate school level and many of them have begun to work from children in the streets, and are even affected families.…”
Section: Quantitative Stagementioning
confidence: 99%
“…In Mexico, the materials recovered to be commercialised afterwards represent 8-12% out of the total generated [37]. In India 6-10% of MSW are recyclables [7], in a Canadian university this value reached 49.3% [16], and in Taiwan, 44.92% [26]. In this study, the value was 16%.…”
Section: Strategies For Waste Managementmentioning
confidence: 49%
“…In the regulation of some countries, solid waste management is the responsibility of local authorities [7]. However, this activity should not only involve public administration, but also waste present both equivalent carbon dioxide (CO 2 eq) emissions and waste reductions in one of the student housings after implementation of a solid waste management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was divided into four sections, which are Section (A): Respondents' Section (B): Attitudes regarding solid waste management and the questions on attitude were adapted from a researcher who investigated the role of attitude and knowledge of households towards solid waste management practices [21]. Section (C): Solid waste management perception and Section.…”
Section: Questionnaire Designmentioning
confidence: 99%